Γ-Fe2O3@Si-(CH2)3@mel@(CH2)4SO3H as a magnetically bifunctional and retrievable nanocatalyst for green synthesis of benzo[c]acridine-8(9H)-ones and 2-amino-4H-chromenes. Issue 5 (18th August 2020) - Karimirad, Fatemeh; Behbahani, Farahnaz Kargar
Abstract: The present work describes the synthesis and characterization of melamine functionalized with sulfonic acid supported on the magnetic nanoparticle, γ-Fe2 O3 @Si-(CH2 )3 @melamine@butyl sulfonic acid nanoparticle as a green and retrievable bifunctional catalyst. This catalyst was assigned by FT-IR, XRD, EDX, TEM, VSM, CHN, and TGA analyses. In addition, the catalytic activity of this new catalyst was investigated for the synthesis of 7, 10, 11, 12-tetrahydrobenzo[c]acridine-8(9 H )-ones from aliphatic and aromatic aldehydes, dimedone and 1-naphthylamine in excellent yields and 2-amino-4 H -chromenes were provided using manufactured nanocatalyst in good-to-high yield under mild reaction condition. The γ-Fe2 O3 @Si-(CH2 )3 @melamine@butyl sulfonic acid heterogeneous catalyst showed the advantages such as very simple and eco-friendly due to use from magnetic nanoparticles as high reusability of the catalyst, magnetically separable catalyst, excellent yield, and mild reaction condition. The synthesis of some new derivatives of dibenzo[ c ]acridines and 2-amino-4H-chromenes in the presence of this nanocatalyst is also reported.